Analisis Pertanggalan Prasasti Wanua Tengah III - nfn. Trigangga (Balai Arkeologi Yogyakarta, 1994)
Inscription as a written source has a very high quality to reconstruct ancient history, because from its contents it can provide an overview of various things that were contemporaneous with the writing of the inscription. Even so, the inscription, like other historical sources, also needs to be tested for the credibility of its contents before being used as material for historical writing. The test in question is through external and internal criticism.